SYSTEMATIC LITERATURE REVIEW: PENINGKATAN KEMAMPUAN BERPIKIR KOMPUTASIONAL MATEMATIS SISWA - Syari, Aulia Kartika; Meiliasari, Meiliasari (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2024)
AbstractMathematical computational thinking ability is one of the mathematics competencies contained in the independent curriculum. This research aims to analyze qualitative studies on mathematical computational thinking skills conducted starting in 2019. The method used is a Systematic Literature Review (SLR), and the analysis used the PRISMA Protocol (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocol). 18 articles were reviewed in this study. All articles used were indexed by Sinta and Scopus and taken from Google Scholar, Scopus, and Garuda. The analysis shows that teachers can use approaches and learning models or develop teaching materials to improve students' mathematical computational thinking skills. This can help teachers in improving students' computational thinking skills. Computational thinking skills can be developed in learning mathematics on materials such as number patterns, building space, number operations, and materials in lectures such as abstract algebra. Abstrak Kemampuan berpikir komputasional matematis merupakan salah satu kompetensi matematika yang termuat dalam kurikulum merdeka. Penelitian ini bertujuan untuk menganalisis studi-studi kualitatif tentang kemampuan berpikir komputasional matematis yang dilakukan mulai tahun 2019. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan analisis yang digunakan PRISMA Protocol (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocol). Terdapat 18 artikel yang dikaji pada studi ini. Semua artikel yang digunakan terindeks Sinta dan Scopus yang diambil dari Google Scholar, Scopus, dan Garuda. Hasil analisis menunjukkan untuk meningkatkan kemampuan berpikir komputasional matematis siswa guru dapat memilih menggunakan pendekatan, model pembelajaran, maupun mengembangkan bahan ajar. Hal ini dapat membantu guru dalam meningkatkan kemampuan berpikir komputasional siswa. Kemampuan berpikir komputasional dapat dikembangkan dalam pembelajaran matematika pada materi seperti pola bilangan, bangun ruang, operasi bilangan, dan materi dalam perkuliahan seperti aljabar abstrak.